Dinâmica populacional e alimentar de Stegastes fuscus, (Osteichthyes:pomacentridae) em arrecifes da praia de Búzius, no Rio Grande do Norte - Canan, Bhaskara (2007)
The damselfish, Stegastes fuscus Cuvier, 1830 (Osteichthyes: Perciformes: Pomacentridae), is abundant in the coastal reefs of Búzios Beach, Rio Grande do Norte, Brazil and they play an important role in the reef community ecology. The present study investigated the feeding strategy of this species considering the food habits and morfo-histology of the digestive tract. Influence of the environmental correlates such as temperature, rainfall and luminosity in the tidal rock pools were studied. The fish were captured on a monthly basis from September 2004 to August 2005, during which period 842 individuals of S. fuscus were captured, 125 males, 437 females and 280 individuals without sex identification. The sex ratio observed was 1 M : 3,5 F. The total body length of males varied from 3.6 to 11.3 cm, with a mean of 7.77 cm; that of females varied from 2.9 to 11.4 cm, with a mean of 7.85 cm, and that of sex grouped individuals varied from 2.9 to 11.4 cm, with a mean of 7.83. However, there was no difference between males and females in total body length. This species presented a positive alometric growth and the equations obtained for the relation between body mass and total body length were: Wt =0,0174Lt 3,1123 for males; Wt =0,0137Lt 3,2294 for females and Wt = 0,0148Lt 3.1928 for sex grouped individuals. The relation between total body length and standard length was L t = 1 ,3223Ls + 0,1527 for sex grouped individual s. February to August was associated to a long period of gonadal resting. The fish spawned during January and in September -October. The frequency of fish with empty stomachs occurred during August to December, whereas frequency of fish with food contents i n stomachs occurred during January to July. This species is considered as a preferential herbivore based on the volume of macroalgae in its diet composition. The morfo -histological aspects of S. fuscus confirm herbivory. Among the environmental factors con sidered only rainfall showed a correlation with the feeding habits of this species